Dark Triad and Sport Performance among Pakistani Players Mediating Role of Antisocial Behavior: A Conceptual Study - Nazar, Naila; Khalid, Nur Haziyanti (EDUCATUM Journal of Social Sciences, 2023)
The study will measure the association between dark triad and sport performance among Pakistani players with mediating role of antisocial behavior. The total sample (N= 495) of Pakistani players will be recruited from an affiliation with a university institute, or club, and national players will be selected in this research. The age range will be 18-35 years of participants. Three instruments will be used to collect the data, Short Dark Triad, and Sport Performance Scale. While in this study Antisocial Behavior Scale will be developed and validated. This study will be conducted in two phases. The phase-1 comprised the exploratory sequential mixed methods research design (tool development) used to explore the domains of antisocial behavior, develop, and validate the antisocial behavior scale. While, phase-2, is quantitative and cross-sectional in nature. The methods and procedures adopted for both phases are given separately. Considering the literature review and objectives of the study, three proposed hypotheses will be tested after the data collection. H1: The indigenous antisocial behavior scale will be valid and reliable among Pakistani players. H2: There will be an association of dark triad personality (Machiavellianism, Narcissism, and Psychopathy) and antisocial behavior with the sports performance of Pakistani players. H3: There will be an influence of dark triad personality (Machiavellianism, Narcissism, and Psychopathy) on the sport performance of Pakistani players with mediating role of antisocial behavior. H4: In the first phase of the study, data will be analyzed through Content Analysis, and in phase 2, the data will be analyzed through SPSS and AMOS to test the psychometrics properties of newly developed Antisocial Behavior Scale, the association between variables and mediation analysis using Structural Equation Modeling. Regarding implications of the study, this study will be helpful for sports psychologists, players, coaches, and sports policymakers. Dark Triad are important personality traits, which can positively and negatively predict sports performance among players. This research will gain the intention of sports psychologists, coaches, and sports policy makers to develop policies regarding personality traits such as dark triad and antisocial behavior. This study recommends to coaches and team selectors during the selection of players, the personality traits of players should also be measured and players who have negative personality traits will be considered for further psychotherapeutic interventions to overcome their negative personality traits, after this so they can enhance their sports performance.